CouchSurfing : experiences, reputation, references and decision-making in an online hospitality network - Franz, Melanie (2014)
The aim of this thesis was to analyse behavioural patterns that occur after a negative experience during a hospitality exchange. The focus of this study is the largest online hospitality network to date, the CouchSurfing Project. CouchSurfing enables travellers to connect and to offer each other help in form of a free hospitality exchange. Furthermore, CouchSurfing presents a platform for cultural exchange and the possibility for members to connect in this online-offline community. As part of a qualitative study, a voluntary online questionnaire has been distributed and answered by 35 CouchSurfing members. The results give insight of how they deal with a negative experience after offline interaction in terms of reference giving and what they do when encountering a negative reference. While the hospitality exchange is build on trust that has been created through various features of the hospitality network, this thesis investigated what happens if trust is violated and how this influences the further actions of its members. As a result, multiple intentions of reference giving or non- reference giving have been identified. These reasons range from reference as reward or punishment, to educational reasons. The underlying thread to decision-making are concerns regarding status and reputation, being it one’s own or those of other members. Furthermore, members’ actions create an apparent paradox. They criticize the flaws of the reputational system as safety generating function, while simultaneously their actual actions and decisions in leaving references neglect to contribute to former.